IDENTIFICATION OF SUITABLE AREAS FOR THE INSTALLATION OF HYDROELECTRIC PROJECTS BASED ON THE STREAM-POWER MODEL - Alves, Alexandre Xavier; Cremon, Édipo Henrique; Alves, Fabio Corrêa; Rabelo, Max Well de Oliveira (Ra'e Ga: o Espaço Geográfico em Análise, 2023)
Hydropower is mostly driven by the river discharge and the gradient slope of the river channels. These two parameters constitute a classical geomorphological model, known as stream-power. Based on the stream-power model, this study aims to identify locations with greater potential for the installation of Small Hydroelectric Power Plants (SHPs) in the Meia Ponte River basin, situated in the central-southern region of the State of Goiás, in Brazil. To achieve this, hydrological data from six hydrometric stations and the Copernicus digital elevation model were utilized to pinpoint areas with higher river power. The results revealed 161.46 km of segments with river power ranging from 5000 to 30000 kW · m-1 and 23 points characterized by pronounced changes in channel slope, indicating a suitable potential for SHP installation. Besides the river-related data considered in this study, future research should encompass various other aspects, including environmental, social, economic, operational, and cultural factors when searching for the best locations for SHP installations.